Cultura financiera y la toma de decisiones financiera en los microempresarios del mercado municipal Requena 2024 - Tuanama Macuyama, Patrick Anderson (2025)
The present final report aimed to determine the relationship between financial culture and financial decision-making in microentrepreneurs of the Requena 2024 municipal market. Where we worked under a basic method, descriptive and correlational level with a non-experimental design, opting for a population of 250 sellers, to whom a questionnaire of questions was used to collect information and data. The results show us that the level of financial culture in microentrepreneurs was rated as regular by 25%, because the microentrepreneurs strongly agree, demonstrating a solid knowledge of the process and regularly using banking services, such as credits, savings programs and insurance; However, the sellers agree with their financial management capacity; while they are undecided about saving for cash purchases. Therefore, the financial decision-making of micro-entrepreneurs has obtained a score of 24%, this is mainly due to the fact that, in most cases, these entrepreneurs adopt strategies to optimize the budget assigned to investments in their businesses. Finally, it was determined that there is a strong and statistically significant positive relationship between financial culture and economic decisions, corroborated by a coefficient of 0.797, and p=0.000.